Geophagia in Nigeria: Perceptions and Practices of Pregnant Mothers versus Possible Health Outcomes - Onyenweaku, Eridiong Ogbonna (The Food and Nutrition Society of Indonesia in collaboration with the Department of Community Nutrition, IPB University, 2023)
This study aimed at ascertaining the perceptions and practices of pregnant mothers on geophagia, as well as highlighting possible health outcomes. For the cross-sectional survey, a structured questionnaire was designed, content-validated by experts, pre-tested and used for data collection. The questionnaires were administered to 200 pregnant mothers at health care facilities in southern Nigeria (particularly in Calabar and Onitsha), who consented to be part of the study. The findings of this study show that about 75% of the pregnant mothers admitted to consuming edible clays both during and after pregnancy with 60% of them stating that it was a safe practice during pregnancy. Also, the results show that income level and educational attainment significantly (p<0.05) influenced the perception and practices of the respondents regarding geophagia. Of the 2 edible clays explored in this study, kaolin clay was more popularly consumed than bentonite clay. With regards to respondents’ health status, none of them admitted to developing anaemia or any chronic disease during pregnancy. In conclusion, edible clays are still commonly consumed by women in Southern Nigeria, irrespective of age and exposure. Scientific reports show that these clays contain appreciable amounts of certain anti-nutrients and heavy metals, hence it is necessary to create awareness on the possible dangers related to their increased consumption, particularly during pregnancy.